Analisis Pengaruh Curah Hujan terhadap Frekuensi Kejadian Banjir di Kabupaten Kotabaru, Kalimantan Selatan - UMMIYATI, ALFI; PUTRI, WENI ANISA; NUR AZIZA, VINTA SABILA; LESMANA, AJENG ARTHAVIA; AZIZ, KHAFIDH NUR (Progressive Physics Journal, 2024)
The accumulation of water on the ground is what causes flooding, whereas rainfall is the amount of rainwater collected in a flat area Rainfall and flooding are two related but distinct concepts. While rainfall refers to the amount of precipitation that falls in a particular area, flooding is the result of excessive water accumulation on the ground. Indonesia can be classified as a country with high rainfall due to its average annual rainfall ranging from 2000 to 3000 millimeters. In cases of heavy rainfall, excessive water discharge can occur. This can result in flooding when the land, rivers, or water reservoirs cannot manage the overflow effectively. Flooding is a common occurrence in Kotabaru Regency located in South Kalimantan, as it is a combination of mountainous regions, coastal areas, land areas, and small islands. The objective of the study is to examine whether flooding is always caused by high rainfall in Kotabaru Regency from January 2018 to December 2022. The correlation analysis is part of the research design, which utilizes secondary data collected and analyzed in Microsoft Excel. The findings suggest that moderate intensity rainfall is responsible for 73.3% of floods that occurred between 2018-2022. Moreover, 26.7% of floods occurred when rainfall is less than 20 mm/day. However, other factors such as monsoons, tropical cyclones, and El-Nino Southern Oscillation (ENSO) can affect the variability of rainfall and inffluence the occurrence of flood in the area.